Necesidad de tipificar como delito en el Código Orgánico Integral Penal, la violencia económica, para garantizar el derecho a la integridad personal - Vinocunga Batallas, Mónica Jaqueline (2015)
The Constitution of the Republic of Ecuador in Article 67 recognizes the family in its various forms. The State shall protect the fundamental unit of society and ensure conditions that promote the achievement of its purposes, shall be based on equal rights and opportunities for its members. Further, the State shall formulate and implement policies to achieve equality between men and women. The literal a), paragraph 3 of Art. 66 of the Constitution of the Republic of Ecuador, guarantees people the right to humane treatment, comprising a) The physical, mental, moral and sexual integrity. The Art. 81 of the body of laws invoked, says the law will establish special and expeditious procedures for the trial and punishment of crimes of domestic violence, sexual, hate crimes and those committed against children, adolescents, youth, people with disabilities, older adults and persons who, by their characteristics, require greater protection. Specialized prosecutors and defenders or advocates for the treatment of these causes, according to the law shall be appointed. The Code of Criminal Integral in article 155, referring to violence against women or members of the nuclear family, says violence is considered any action that consists of maltreatment, physical, psychological or sexual executed by a family member in against women or other members of the family. Are considered household members to or spouse, the couple in union or union, partner, parents, children, siblings, relatives up to the second degree and persons with whom it is determined that the processing processed or maintains or has maintained family, intimate, emotional, marital, coexistence, dating or cohabiting relationships. Thus criminalizes against the family, physical, psychological or sexual violence. As for physical violence indicates that the person who, as a manifestation of violence against women or members of the family, cause injury, shall be liable to the same penalties for the crime of injuries increased by a third. Psychological violence against women or members of the family, refers to the person who causes harm to the mental health acts of disruption, threats, manipulation, blackmail, humiliation, isolation, surveillance, harassment or control beliefs, decisions or actions shall be punished as follows: 1. If minor damage affecting any of the dimensions of the overall functioning of the person in the cognitive, affective, somatic, areas of behavior and relationships, without causing impairment in performing daily activities is caused, shall be punished by imprisonment of thirty to sixty days. 2. If it affects moderately in any of the areas of personal, work, school, family or social functioning that would be prejudicial in meeting their daily activities and therefore requires specialized mental health treatment, you will be punished six months to a year. 3. If causes severe psychological damage that even with the specialized intervention has not been reversed, shall be punished with imprisonment of one to three years. The art. 158 of the Act punishes sexual violence against women or members of the family to whom it is imposed to another and forced to have sexual intercourse or other similar practices, shall be liable to the penalties provided in crimes against sexual integrity and reproductive. Sets equally as contravention of violence against women or members of the household, the person who hurt, injured or hit the woman or household members, causing injury or disability not exceeding three days, shall be punished by imprisonment freedom from seven to thirty days. Although, somehow, on psychological violence briefly referred to acts of humiliation, blackmail, threats, isolation and harassment is not referred to acts perpetrated by any mimbro family to control or limit access to their assets, property or income, the victim, resulting in acts of economic violence and that for purposes of administering justice fairly, must be established by the Comprehensive Criminal Code. As the criminal law is very clear notes that in criminal matters is not applicable to the broad interpretation of the rules, but the strict than it says it tenor. In my opinion I believe that in order to protect the rights of victims of acts of economic violence, defined this as all acts or omissions that affect the economy and livelihoods of women, through restrictions aimed at controlling the entry of economic perceptions, restriction, limitation and / or unjustified denial for economic resources, it is necessary to criminalize economic violence to protect the rights of victims of acts of domestic violence